Capital Market Development : Whither Latin America ? - Schmukler, Sergio L. 1997- (The World Bank, 2007)
Over the past decades, many countries have implemented significant reforms to foster capital market development. Latin American countries were at the forefront of this process. The authors analyze where Latin American capital markets stand after these reforms. They find that despite the intense reform effort, capital markets in Latin America remain underdeveloped relative to markets in other regions. Furthermore, stock markets are below what can be expected, given Latin America's economic and institutional fundamentals. The authors discuss alternative ways of interpreting this evidence. They argue that it is difficult to pinpoint which policies Latin American countries should pursue to overcome their poor capital market development. Moreover, they argue that expectations about the outcome of the reform process may need to be revisited to take into account intrinsic characteristics of emerging economies. The latter may limit the scope for developing deep domestic capital markets in a context of international financial integration